Granulocyte colony stimulating factor exacerbates antineutrophil cytoplasmic antibody vasculitis. Issue 6 (19th October 2012) - Freeley, Simon J; Coughlan, Alice M; Popat, Reena J; Dunn-Walters, Deborah K; Robson, Michael G
Abstract : Objectives: Granulocyte colony stimulating factor (GCSF) is important in mobilising neutrophils from the bone marrow but also has a range of proinflammatory effects. We therefore decided to investigate the role of GCSF in antineutrophil cytoplasmic antibody (ANCA) vasculitis. Methods: We measured GCSF levels in the serum of 38 patients with active ANCA vasculitis compared with 31 age-matched controls, and assessed the effect of GCSF priming on the response of human neutrophils to ANCA. We also examined the effect of exogenous GCSF administration in a murine model of antimyeloperoxidase (anti-MPO) vasculitis, and the effect of GCSF on murine neutrophil activation. Results: The serum levels of GCSF in patients with active ANCA vasculitis were significantly higher than those of age matched healthy controls (mean 38.04 vs 18.35 pg/ml, p<0.001). Furthermore, we demonstrated that GCSF primed human neutrophils in vitro for a respiratory burst in response to anti-MPO ANCA. In an anti-MPO antibody transfer model, mice given GCSF had more crescents (mean 29.1% vs 5.8% per glomerular cross section, p<0.05), more macrophages (mean 3.2 vs 1.2 per glomerular cross-section, p<0.01), higher serum creatines (mean 13.6 vs 8.3 μmol/l, p<0.05) and more haematuria (p<0.05) compared with controls. In vivo administration of GCSF with lipopolysaccharide (LPS), but not LPS alone, led to upregulation of CD11c on murine neutrophils. Conclusions: These data suggest that GCSF, which is raised in patient serum, may play an important role in exacerbating disease in ANCA vasculitis. In addition, GCSF therapy for neutropenia should be used with caution in these patients.